The rebirth of fertility: the Trotula and her travelling companions c. 1200-1450 - Tyers, Theresa Lorraine (2012)
This thesis examines to what extent women were involved in their own healthcare and that of others, in the late medieval period. It starts from the observation that modem text editing practices often exclude from discussion other widely disseminated texts that formed the 'travelling companions' of a manuscript - in this case particularly the ensemble known as the Trotula. By focusing on one specific text within the manuscript compilations, the diverse and widespread dissemination of women's knowledge of healthcare and the use of vernacular texts have been marginalised. The thesis argues that the consideration of these 'travelling companions' can offer an alternative view of women's involvement in healthcare, despite the seeming female exclusion from the culture of book-learning and the development of professional licensing in the later Middle Ages. The corpus of manuscripts examined is taken from a range of vernacular compilations produced in England, Flanders and Italy, with some discussion of ownership and transmission of these into the Early Modem period. A number of transcriptions and close readings of the contents are used to identify the discrete characteristics of each copy and to track changes that took place during the transmission process. Detailed comparisons demonstrate that conscious, active choices were made in both the adaptation and interpretation of the material being copied. Analysis of these manipulations reveals that the production of vernacular texts enabled easier consultation and use. The manuscripts point to women's continuing engagement with both the texts and the practice of self-care and that, despite the increase in the number of professional male practitioners over the period, women continued to offer advice to others well into the sixteenth century.